1999
DOI: 10.1007/pl00013177
|View full text |Cite
|
Sign up to set email alerts
|

Distal Pulse Palpation: Is It Reliable?

Abstract: The aim of this study was to evaluate the reliability of distal pulse palpation. The dorsalis pedis and the tibialis posterior arteries of 25 patients with suspected lower limb arterial disease were independently palpated by three vascular surgeons and three medical students in the outpatient clinic and by two vascular nurses and one physician in the vascular laboratory. The palpation findings were compared to the ankle/brachial index (ABI). Palpable and unpalpable pulses were best separated with ABI 0.76 as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 7 publications
(13 reference statements)
3
44
0
4
Order By: Relevance
“…This corroborates our systematic review results: DPN and PVD clinical collection methods seem relatively unimportant (4,15). Although several authors have described the foot pulse palpation to have low sensitivity (16,17), the SWM application procedure does not have consensus (18,19) and the tuning fork has low reliability (19); several studies have shown that these simple methods can be implemented for both community (2,8,15,19,20) and high risk (3, 4) setting diabetic foot screening, independently of the variables collection method.…”
Section: Discussionsupporting
confidence: 86%
“…This corroborates our systematic review results: DPN and PVD clinical collection methods seem relatively unimportant (4,15). Although several authors have described the foot pulse palpation to have low sensitivity (16,17), the SWM application procedure does not have consensus (18,19) and the tuning fork has low reliability (19); several studies have shown that these simple methods can be implemented for both community (2,8,15,19,20) and high risk (3, 4) setting diabetic foot screening, independently of the variables collection method.…”
Section: Discussionsupporting
confidence: 86%
“…Circulation was assessed by palpating the dorsalis pedis; it was defined as good if a pulse was present and poor if a pulse was weak or absent. The reliability of this measure has previously been demonstrated to be 'good' (kappa) [22] under unhurried conditions, using trained professionals. Cognitive impairment was measured using the Clifton Assessment Procedure for the Elderly (CAPE) [23].…”
Section: Baseline Measuresmentioning
confidence: 97%
“…[29][30][31][32] A more reliable method to assess cardiovascular health is warranted. It has been recommended that patients at risk for hypoxic conditions be monitored using pulse oximetry.…”
Section: Conceptual Model Of Pulse Oximetry In a Chiropractic Settingmentioning
confidence: 99%